Proceedings of the Sixth Annual Meeting of Agro-Climatic Regional Planning Project May 13 and 14 , 1994 - Planning Commission (Planning Commission, 1994)
The ACRP Project had carried out a detailed exercise in preparing District/sub-District strategies/plans using the similar approach which had been adopted at Zone and State levels. This exercise as indicated earlier has been carried out for thirty-five districts of the country covering varied agro-climatic, socio-economic and institutional situations. The district level exercise as it stands now has not been integrated with the existing planning process and development mechanisms. Thus, there is a felt-need in the current phase of the exercise to integrate this ACRP approach with the existing planning process, primarily at the district level the thereby at the state level. This phase of the exercise termed as "institutionalisation" can be achieved through a number of alternative methods including training, case studies, documentation etc. In order to operationalize this approach it was considered necessary to involve officials at different levels; state, district and sub-district and also non-officials and professionals engaged in similar tasks. The important consideration is that the basic thrust of ACRP in terms of integrated area based strategy for land and water development with explicit consideration of sustainability and reliability should be maintained in such exercises.
Agro Climatic Regional Planning Unit Planning Commission
Agro Climatic Regional Planning Unit Planning Commission